PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING MENGGUNAKAN MEDIA MICROSOFT FRONTPAGE DAN AKTIVITAS BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA KELAS X SMA - Sidabutar, Ropinus (JGK (Jurnal Guru Kita), 2020)
Abstract: The Effect of Problem Based Learning Model Using Microsoft Frontpage Media and Learning Activities on Mathematics Learning Outcomes of Class X Senior High School. The purpose of this study was to see (a) the effect of problem based learning using Microsoft Frontpage media on mathematics learning outcomes of high school students, (b) the effect of learning activities on high school students’ mathematics learning outcomes, (c) the effect of the interaction between problem based learning. by using Microsoft Frontpage media with learning activities on Mathematics learning outcomes. The population in this study were all class X students at SMA Negeri 1 Sibabangun consisting of 3 classes for the 2019/2020 school year. The sampling technique was carried out by means of purposive sampling. The research sample consisted of the experimental class and the control class. The experimental class was taught by learning problem-based learning with microsoft frontpage media, namely class X-2 and class control taught by learning media microsoft frontpage, namely class X-3. The instruments used in this study were a learning outcome test and a learning activity questionnaire. Student learning outcomes using problem-based learning with Microsoft Frontpage media an average gain of 0.38 is higher than the average gain value of student learning outcomes taught using Microsoft Frontpage media of 0.24. The average gain of learning activities is 0.4. Keywords: Problem Based Learning, Microsoft Frontpage, Learning Activities Abstrak: Pengaruh Model Pembelajaran Problem Based Learning Menggunakan Media Microsoft Frontpage Dan Aktivitas Belajar Terhadap Hasil Belajar Matematika Kelas X Sma. Tujuan dari penelitian ini adalah untuk melihat (a) pengaruh pembelajaran problem based learning dengan menggunakan media Microsoft Frontpage terhadap hasil belajar Matematika siswa SMA, (b) pengaruh aktivitas belajar terhadap hasil belajar Matematika siswa SMA, (c) pengaruh interaksi antara pembelajaran problem based learning dengan menggunakan media microsoft frontpage dengan aktivitas belajar terhadap hasil belajar Matematika. Populasi dalam penelitian ini yaitu seluruh siswa kelas X di SMA Negeri 1 Sibabangun terdiri dari 3 kelas tahun ajaran 2019/2020. Teknik pengambilan sampel dilakukan dengan cara purposive sampel. Sampel penelitian terdiri atas kelas eksperimen dan kelas kontrol. Kelas eksperimen diajarkan dengan pembelajaran problem based learning dengan media microsoft frontpage yaitu kelas X-2 dan kelas kontrol diajarkan dengan pembelajaran media microsoft frontpage yaitu kelas X-3. Instrumen yang digunakan dalam penelitian ini adalah tes hasil belajar dan kuisioner aktivitas belajar. Hasil belajar siswa menggunakan pembelajaran problem based learning dengan media Microsoft Frontpage rata-rata gain sebesar 0,38 lebih tinggi dari nilai rata-rata gain hasil belajar siswa yang diajarkan dengan menggunakan media microsoft frontpage sebesar 0,24. Rata-rata gain aktivitas belajar sebesar 0,4. Keywords : Problem Based Learning, Microsoft Frontpage, Aktivitas Belajar